ASSESSING THE LEGAL STATUS OF LIMITED PARTNERSHIP (CV) - Nadapdap, Binoto (Indonesia Law Review, 2013)
Business actors can choose various kinds of business entities to run their business. The law gives business actors the freedom to decide which business entity to use as a vehicle for their business activities. From a multitude of businesses, essentially there are three forms, which are: individual proprietorship, partnership and limited liability company. Additionally, there are some that have the opinion that there are two categories of companies: companies that are legal entities and those which are not legal entities.